The Effect of Normal Push-Up and Modified Push-Up Exercises on Bowling Ability In Athletes Cricket FIKK UNM - Anwar, Nur Indah Atifah; Hasmyati, Hasmyati (UNIVERSITAS NEGERI MAKASSAR, 2025)
This study aims to analyze the effect of normal push-up and modified push-up training on bowling performance in cricket athletes at FIKK UNM. The research sample consisted of athletes divided into two groups: one group underwent normal push-up training, while the other performed modified push-up training. The results showed that normal push-up training improved bowling performance from a pre-test average of 25.2000 to a post-test average of 42.2000, with a difference of 17.0000 and a P-value of 0.007 (P<0.05), indicating a significant effect. Meanwhile, modified push-up training improved performance from a pre-test average of 20.0000 to a post-test average of 41.9000, with a difference of 20.9000 and a P-value of 0.003 (P<0.05), also demonstrating a significant effect. A comparison between the two training methods revealed that modified push-up training had a greater impact on improving bowling performance than normal push-up training. Therefore, modified push-up training is recommended as a more effective method for enhancing bowling performance in cricket athletes at FIKK UNM.